2017
DOI: 10.36076/ppj.2017.e220
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Post-herpetic Neuralgia from Dream to Reality: A Ten-step Model

Abstract: Herpes zoster (HZ) is a painful, blistering skin eruption in a dermatomal distribution caused by reactivation of a latent varicella zoster virus in the dorsal root ganglia (DRG). Post-herpetic neuralgia (PHN) is the most common complication of acute herpes zoster (AHZ). Severe prodrome, greater acute pain and dermatomal injury, and the density of the eruption are the risk factors and predictors for developing PHN. PHN has a substantial effect on the quality of life; many patients develop severe physical, occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…5,6,22 On the other hand, in the sensitized/preserved phenotype, it might be more important to prevent further mechanisms of pain chronification, ie, by a more aggressive analgesic treatment. 3,4,12,17,23…”
Section: Discussionmentioning
confidence: 99%
“…5,6,22 On the other hand, in the sensitized/preserved phenotype, it might be more important to prevent further mechanisms of pain chronification, ie, by a more aggressive analgesic treatment. 3,4,12,17,23…”
Section: Discussionmentioning
confidence: 99%
“…However, no rigid guideline for HZ management has been established until now. Previous studies suggested that management for HZ should include treatment for acute viral infection, early intervention to reduce HZ‐associated pain, and prevention of PHN . Our study was the first to apply ultrasound‐guided CRB in the lower cervical HZ during the acute period.…”
Section: Discussionmentioning
confidence: 87%
“…Pacienţii a căror durere este refractară la tratamentele noninvazive pot recurge la tratamente intervenţionale. Luând în considerare cât de invazivă este tehnica, profilul de siguranţă şi costurile, se recomandă iniţial intervenţii precum injectarea subcutanată a toxinei botulinice tip A, stimularea nervului periferic, stimularea nervilor electric transcutanat, blocul nervos periferic şi blocul ganglionului stelat, urmate de blocul paravertebral şi radiofrecvenţa pulsată (28,29). În cazul persistenţei durerii de severitate crescută, se pot realiza stimularea măduvei spinării, injecţii intratecale cu metilprednisolon sau distrugerea ganglionului ră-dăcinii dorsale, având în vedere balanţa risc-beneficiu (28,30).…”
Section: Tratament Intervenţionalunclassified